Bringing satellite and nanotechnologies together: unifying strengths against pollution and climate change - Ferral, Anabella; Bonansea, Matías; Scavuzzo, Carlos Marcelo; Nemiña, Francisco; Burgos Paci, Maximiliano; Ramirez, Jessica Casandra; Sepúlveda, Borja; Fraxedas, Jordi; Esplandiu, Maria Jose (Frontiers in Nanotechnology, 2024)
Nowadays, we witness remarkable technological progress alongside unprecedented challenges that threaten the delicate balance of our planet's ecological system. Environmental contamination plays a central role in this, with rapid urbanization, industrialization, mining and agricultural practices intensifying the introduction of pollutants into the environment. This article highlights the potential synergy between two fields operating at vastly different scales: satellite technology and nanotechnology. This article delves into the offerings of each of these disciplines and examines how they can mutually contribute to the detection, prevention and mitigation of environmental pollution. Satellites play a crucial role in identifying and monitoring large-scale polluted areas, offering comprehensive insights into environmental challenges. They are indispensable in tracking air, water pollution levels, assessing land degradation, and monitoring changes in ocean health with relatively high spatial and temporal resolution. Nanotechnology leverages the unique properties of materials at sub-micron scale by offering amplified chemical reactivity and new optical, electronic, and magnetic attributes, enabling selective and sensitive sensors and rapid and efficient contaminant capture/degradation strategies. Emerging nanomaterials, along with nature-inspired and self-powered or self-sustaining designs, broaden capabilities for efficient solutions. Advanced nanocharacterization techniques deepen material understanding and quantification, while nanofabrication allows precise design of functional nano-devices. We believe the synergistic relationship between both fields can yield cooperative solutions, expediting effective measures and greatly influencing policy decisions. This article advocates for the collaboration between these two disciplines to foster impactful progress in facing global challenges.